Alternative method for intramuscular fat analysis using common laboratory equipment. (May 2015) - Segura, J.; Calvo, L.; Óvilo, C.; González-Bulnes, A.; Olivares, A.; Cambero, M.I.; López-Bote, C.J.
Abstract: A procedure to quantify intramuscular fat was developed using common inexpensive laboratory equipment. Three homogenization methods of lyophilized muscle samples (Ball-mill, Grinder and Mortar) and two extraction methods (Ball-mill or Vortex) were used in turkey meat and pork. Two-hundred mg of lyophilized and homogenized samples were accurately weighed and mixed with 1.5 mL of dichloromethane–methanol (8:2) and shaken either in a Mixer Mill (MM400, Retsch Technology) or in a Vortex. The final mixture was separated by centrifugation. Solvent was evaporated under a nitrogen stream and lipid content was gravimetrically determined. Besides, it was checked that the fatty acid profile was not altered by the protocol used. Moreover, the analysis of 4 replicas from the same sample showed different variation coefficients (16–29%) for the new procedures proposed over a wide range of IMF content. The combination of Grinder and Vortex methodologies can be proposed as a simple and inexpensive alternative to previous ones. Highlights: A laboratory procedure for intramuscular fat analysis was optimized. This procedure uses common inexpensive laboratory equipment. The use of Mortar as a homogenization method leads to high imprecise results. Vortex can be an alternative extraction method.